PENGARUH STORE ATMOSPHERE TERHADAP KEPUTUSAN PEMBELIAN PRODUK PADA MINIMARKET BORNEO TANJUNG (p3m.stiatabalong.ac.id, 2022)
The Influence of Store Atmosphere on Product Purchasing Decisions at Borneo Tanjung Minimarket. One of the considerations in making purchasing decisions is an attractive store atmosphere. Store atmosphere can affect the feelings or mood of consumers who visit the store so that it influences and enhances purchasing decisions. The purpose of this study was to determine the effect of: 1) To determine and analyze the effect of store atmosphere on product purchasing decisions at Borneo Tanjung Minimarket; 2) To determine the magnitude of the influence of store atmosphere on product purchasing decisions at Borneo Tanjung Minimarket. This research uses quantitative methods. The average number of population is 417 people in 1 day, which is used as a sample in this study as many as 80 respondents. The sample technique used in this study is the Accidental Sampling technique. The questionnaire is the main instrument for collecting data. The data analysis technique uses a simple linear regression analysis test using SPSS Version 26 software. The results show that (1) There is a significant influence of Store Atmosphere (X) on Purchase Decision (Y) at Minimarket Borneo Tanjung, because the tcount is greater than the value ttable and the significant value is less than 0.05 so that H0 is rejected and Ha is accepted; (2) The magnitude of the influence of the Store Atmosphere on purchasing decisions is 63.4%, the remaining 36.6% is influenced by other variables outside of the variables tested, such as price, service quality, and product quality. Keywords: Store Atmosphere, Purchase Decision.